2022
DOI: 10.3390/vaccines10060878
|View full text |Cite
|
Sign up to set email alerts
|

An Integrative Analysis of the Immune Features of Inactivated SARS-CoV-2 Vaccine (CoronaVac)

Abstract: Currently, an inactivated vaccine has been widely used with encouraging results as a prophylactic agent against COVID-19 infection, which is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and its variants. However, in vitro SARS-CoV-2 vaccine-specific immune features remain elusive, hindering the promotion of a third dose of the vaccine. Here, we present a detailed in vitro immune cellular response and large-scale multi-omics analysis for peripheral blood mononuclear cells (PBMCs) from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 40 publications
5
11
0
Order By: Relevance
“…A clinical study focusing on the immunology of 71 confirmed COVID-19 cases found that complement component C1q dropped in severe COVID-19 patients significantly compared with mild-ill patients ( 31 ). The CoronaVac-induced regulation of complement C1q subcomponent was also detected by Jiang et al ( 19 ).…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…A clinical study focusing on the immunology of 71 confirmed COVID-19 cases found that complement component C1q dropped in severe COVID-19 patients significantly compared with mild-ill patients ( 31 ). The CoronaVac-induced regulation of complement C1q subcomponent was also detected by Jiang et al ( 19 ).…”
Section: Discussionsupporting
confidence: 57%
“…Since the cytokines were measured from serum without the knowledge of production cells and were only measured on two days, further information on the role of the cytokines in CoronaVac vaccination cannot be obtained in this study. Zhao et al (18) and Jiang et al (19) have studied the regulation of cytokines and lymphocytes induced by CoronaVac in a comprehensive way in their respective studies. Jiang et al characterized the lymphocyte subpopulations before and after vaccination, and found that after the second vaccination, CD8+ cytotoxic T cell levels decreased and the serum NAbs titers increased (19), in consistent with our results, which can suggest a balance between cellular and humoral immune responses dominating at early and late stages of vaccination, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations